An international, multicentre evaluation and description of Burkholderia pseudomallei infection in cystic fibrosis. Issue 1 (December 2015) - Geake, James; Reid, David; Currie, Bart; Bell, Scott
Abstract Background Several cases ofBurkholderia pseudomallei infection in CF have been previously reported. We aimed to identify all cases globally, risk factors for acquisition, clinical consequences, and optimal treatment strategies. Methods We performed a literature search to identify all published cases ofB. pseudomallei infection in CF. In addition we hand-searched respiratory journals, and contacted experts in infectious diseases and CF around the world. Supervising clinicians for identified cases were contacted and contemporaneous clinical data was requested. Results 25 culture-confirmed cases were identified. The median age at acquisition was 21 years, mean FEV1 % predicted was 60 %, and mean BMI was 19.5 kg/m2 . The location of acquisition was northern Australia or south-east Asia for most. 19 patients (76 %) developed chronic infection, which was usually associated with clinical decline. Successful eradication strategies included a minimum of two weeks of intravenous ceftazidime, followed by a consolidation phase with trimethoprim/sulfamethoxazole, and this resulted in a higher chance of success when instituted early. Three cases of lung transplantation have been recorded in the setting of chronicB. pseudomallei infection. Conclusion Chronic carriage ofB. pseudomallei in patients with CF appears common after infection, in contrast to the non-CF population. This is often associated with an accelerated clinical decline. Lung transplantation has been performed in select cases of chronicB. pseudomallei infection.